EFEKTIVITAS MEDIA PEMBELAJARAN BUKU CERITA BERGAMBAR DALAM MENINGKATKAN KEMAMPUAN STORYTELLING PADA SISWA MIS ISLAMIYAH GUPPI - Muliatik, Sri; Wulandari, Wina; Zahara, Siti Fatimah (Fakultas Agama Islam Universitas Al Washliyah, 2024)
This study aims to explore the effectiveness of picture storybook learning media in improving the storytelling skills of MIS Islamiyah GUPPI students. The method used is an experiment with pre-test and post-test design. The research subjects consisted of grade IV students at MIS Islamiyah GUPPI. In the early stages, students are given the habit of visiting the school library every 1 week 2 times and literacy activities every Saturday every two weeks. Students were given a pre-test to measure their storytelling skills before the intervention. During the four meetings, students used picture story books as a learning medium, which included a variety of stories with interesting illustrations and prophetic stories. After the intervention period, students underwent a post-test to measure the improvement of their storytelling skills in telling stories about prophets. The results of the analysis showed a significant improvement in students' storytelling skills, with an average pre-test score of 65 and an average post-test score of 85. These findings indicate that picture storybooks are an effective medium in improving storytelling skills, strengthening students' communication skills and literacy. This study suggests that educators integrate picture story books more often in learning to support the development of students' storytelling skills.